BRICS countries and their biosafety measures in dental clinics during the COVID-19 pandemic (Research, Society and Development, 2021)
The pandemic caused by the new coronavirus has led to the need for the adoption of biosafety guidelines for dental care, establishing preventive measures to contain the spread of the virus. The present study aims to identify, differentiate and compare the protocols of biosafety and dental care after COVID-19 among the BRICS member countries (Brazil, Russia, India, China and South Africa), guiding dental practice safely and effectively. This is a documentary, descriptive, qualitative and quantitative study, in which decrees and manuals made available at the sites of regulatory authorities were selected, about the biosafety protocols applied to dentistry during the pandemic. Among the results of this study, it was identified that all BRICS member countries placed as mandatory for dental clinics to follow a care protocol, tendon as the basis of the regulatory authorities of the country itself; Brazil was the country with the highest number of official publications on care during dental care, followed by Russia and India; China was the country with the lowest number of adaptations, since it already had well-established protocols due to other infections that plague the country. It is concluded that the countries that integrate the BRICS, through their regulatory authorities, provide a protocol for service after COVID-19, with emphasis on the use of Face Shield, masks N95 and PFF2, as well as waterproof coats and aprons, mainly in procedures that generate aerosols.